PLANKTONIC FORAMINIFERA: PROBLEMS OF TERMINOLOGY AND A NEW SPECIES FROM THE UPPER ALBIAN OF THE NORTHERN CAUCASUS - Gorbatchik T.N.; Alexandrova A.A. (My University, 2001)
Questions of terminology characterizing the ornamentation and porosity of foraminiferan tests are discussed. A new species Hedbergella accurata is described from the Upper Albian (Stolizkaia dispar Zone) of Baksan and Kheu River Basins. The species is distinguished by the presence of four chambers in the last coil, ornamentation represented by small tubercles (muricae) and microperforation of the wall.
Keywords: Albian; Terminology; Foraminifera; Мезозой::Меловая::Нижний::Альбский; Mesozoic::Cretaceous::Lower::Albian